2019
DOI: 10.1038/s41598-019-56140-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tuberculous empyema in pleural tuberculosis patients

Abstract: Tuberculous empyema (TE) is associated with high mortality and morbidity. In the retrospective cohort study, we aimed to find risk factors for TE among pleural tuberculosis (TB) patients. Between July 2011 and September 2015, all culture-confirmed pleural TB patients (474 cases) were enrolled in our study. Empyema was defined as grossly purulent pleural fluid. Demographic and epidemiological data were collected for further analysis. Multivariate logistic regression analysis was used to evaluate risk factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
2
11
0
5
Order By: Relevance
“…[ 5 ] Although the majority of pleural TB patients are cured after treatment with standardized anti-TB regimens, a small proportion of patients progress to tuberculosis empyema (TE) in spite of medical treatment, [ 6 ] further leading to formation of chronic and fatal sequelae. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Although the majority of pleural TB patients are cured after treatment with standardized anti-TB regimens, a small proportion of patients progress to tuberculosis empyema (TE) in spite of medical treatment, [ 6 ] further leading to formation of chronic and fatal sequelae. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…17 The study by Wen et al conducted in 2019 had reported a decrease in the incidence of tubercular related fibrothorax but an increase in the pyogenic infective etiology more so in children. 18 A study conducted by Kundu et al in the Indian subcontinent region identified that of the 75 cases of empyema seen during their one and half year period 29 cases (38.7%) were of tuberculosis etiology and 46 (61.3%) were due to non-tubercular etiology with staphylococcus aureus being the most common. 19 All the patients were investigated for culture and sensitivity from the bronchial wash specimens taken during bronchoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…However, ADA is also present in hepatocytes, and when hepatocytes are damaged, the ADA level in the peripheral blood increases [15]. For example, the ADA level is notably elevated in Mycobacterium tuberculosis infection, autoimmune diseases, hepatitis, and malignant tumors [2][3][4]16]. Thus, ADA's expression and activity increase significantly during inflammation, and monocytes and macrophages are important sources of extracellular ADA [17].…”
Section: Discussionmentioning
confidence: 99%